POLITIK ANGGARAN BELANJA DESA MASA PANDEMI DI KALURAHAN SUMBERMULYO, BAMBANGLIPURO, BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Tyas, Hari Saptaning; Winarti, Safitri Endah; Raharjo, Triyanto Purnomo; Puspitasari, Condrodewi (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2022)
Changes to the APBDes were observed to have occurred 3 times in 2020 during the pandemic at Sumbermulyo Ward in Bambanglipuro, Bantul, with reallocation of the field for village government administrations being the minority percentage-wise. The purpose of this research is to described the politics surrounding budgeting during the pandemic. This research using an interpretative qualitative method, and using observations, interviews, FDGs and documentation as data collection methods. Respondents consist of 13 informants. Results have indicated that deliberation had occurred because the ward government is faced of various conflicting interests by stakeholders, even though the supra-village government wants depoliticization by issuing various rules that must be implemented by the village. Contestation taken by different parties in the village, especially the hamlet heads who maintained physical development programs in their own hamlets. Participation of villagers has been relatively low as the process of budget allocations change are discussed at the village level, by passing hamlets forum. The majority of the budget distribution is allocated to the village government administrations. The authority and capacity of the parties in the village tend to be weakened by prioritizing over factors of “humanness” and “fast responses” in their response to handling the pandemic.